PROCEDURAL CHALLENGES IN CIVIL LAWSUITS RELATED TO MEDICAL MALPRACTICE: THE ROLE OF RECOMMENDATIONS FROM THE PROFESSIONAL HONOUR COUNCIL IN INDONESIA - Gunawan Widjaja; Hotmaria Hertawaty Sijabat (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2025)
Medical malpractice cases in Indonesia have increased in line with growing public awareness of the right to adequate health services. Civil lawsuits are often filed on the basis of unlawful acts, but the process faces various procedural challenges, particularly in terms of evidence, access to medical records, and the application of medical professional standards. Judges often find it difficult to interpret dynamic medical standards within the rigid framework of civil procedural law. To that end, the Professional Ethics Council (MKP) serves as an institution that provides recommendations regarding alleged violations of professional standards. MKP recommendations play an important role in helping judges understand technical medical aspects, although their status is still debated as to whether they are merely additional considerations or have binding force. This study uses a library research method with a normative juridical approach to legislation, court decisions, and related scientific literature. The results show that procedural challenges in civil medical malpractice lawsuits are not only related to technical aspects of evidence but also to the legal uncertainty of the MKP's recommendations. Therefore, regulatory clarification is needed to establish MKP recommendations as expert evidence that can be tested in court, thereby providing balanced legal certainty for patients and medical personnel.